2002
DOI: 10.1002/ps.487
|View full text |Cite
|
Sign up to set email alerts
|

Molluscicidal and anti‐feedant activities of diterpenes from Euphorbia paralias L

Abstract: Nine known diterpene polyesters of segetanes, jatrophenes and paralianes have been isolated from the aerial parts of Euphorbia paralias L. The molluscicidal activity of isolated compounds was evaluated on Biomphalaria alexandrina (Ehrenberg). Paraliane diterpene, (2S,3S,4R,5R,6R,8R,12S,13S,14R,15R)-5,8,14-triacetoxy-3-benzoyloxy-15- hydroxy-9-oxo-paraliane, was the most potent compound against the snail. Anti-feedant activity was tested by a conventional leaf disc method against third-instar larvae of Spodopte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…Therefore, it could be concluded that compounds 1 – 3 exhibited antifeeding activity against S littoralis in a concentration‐dependant manner. The antifeedant activities of the isolated limonoids ( 1 – 4 ) were stronger than the activities of a limonid toosendanin isolated from Melia toosendan Seib ex Zucc,16 diterpenes from Salvia spp17 and Euphorbia paralias L18 but weaker than the well‐known antifeedant azadirachtin from Azadirachta indica A Juss 19. This finding agreed with our previous study15 in which the compounds 1 – 4 showed a minimum antifeedant inhibition concentration at 300 µg ml −1 when evaluated by conventional leaf‐choice‐disk method, while azadirachtin showed the minimum antifeedant inhibition concentration at 50 µg ml −1 .…”
Section: Resultsmentioning
confidence: 90%
“…Therefore, it could be concluded that compounds 1 – 3 exhibited antifeeding activity against S littoralis in a concentration‐dependant manner. The antifeedant activities of the isolated limonoids ( 1 – 4 ) were stronger than the activities of a limonid toosendanin isolated from Melia toosendan Seib ex Zucc,16 diterpenes from Salvia spp17 and Euphorbia paralias L18 but weaker than the well‐known antifeedant azadirachtin from Azadirachta indica A Juss 19. This finding agreed with our previous study15 in which the compounds 1 – 4 showed a minimum antifeedant inhibition concentration at 300 µg ml −1 when evaluated by conventional leaf‐choice‐disk method, while azadirachtin showed the minimum antifeedant inhibition concentration at 50 µg ml −1 .…”
Section: Resultsmentioning
confidence: 90%
“…Natural molluscicidal organic compounds include a variety Preliminary investigation of the disposition of the molluscicidal saponin deltonin from Balanites aegyptiaca in a snail species (Biomphalaria glabrata) and in mice of substance classes such as coumarins, 6) diterpenes, 7) alkaloids 8) and saponins. 9,10) Several saponins were investigated as pesticides for the control of snails, which are vectors for Schistosomiasis.…”
Section: Introductionmentioning
confidence: 99%
“…In order to enable a clear 262 A. K. Hundsdoerfer et al CHEMOECOLOGY identification of the experimentally administered TPA in the larval tissues, E. myrsinites was thus chosen as food plant for the caterpillars in our experiments. The diterpene esters from E. paralias have been shown to exhibit molluscicidal and anti-feedant properties (Abdelgaleil et al 2002) and those of Jatropha curcas (Euphorbiaceae) to exhibit insecticidal activities against several species of e.g. moths, butterflies, aphids, bugs, bettles, flies and cockroaches (Wink et al 1997).…”
Section: Introductionmentioning
confidence: 99%